On the Origin of the Improvement of Electrodeposited MnOx Films in Water Oxidation Catalysis Induced by Heat Treatment. Issue 11 (4th May 2015) - Khan, Munirah; Xiao, Jie; Zhou, Fengling; Yablonskikh, Mikhail; MacFarlane, Douglas R.; Spiccia, Leone; Aziz, Emad F.
Abstract Manganese oxides (MnOx) are considered to be promising catalysts for water oxidation. Building on our previous studies showing that the catalytic activity of MnOx films electrodeposited from aqueous electrolytes is improved by a simple heat treatment, we have explored the origin of the catalytic enhancement at an electronic level by X‐ray absorption spectroscopy (XAS). The Mn L‐edge XA spectra measured at various heating stages were fitted by linear combinations of the spectra of the well‐defined manganese oxides—MnO, Mn3O4, Mn2O3, MnO2 and birnessite. This analysis identified two major manganese oxides, Mn3O4 and birnessite, that constitute 97 % of the MnOx films. Moreover, the catalytic improvement on heat treatment at 90 °C is related to the conversion of a small amount of birnessite to the Mn3O4 phase, accompanied by an irreversible dehydration process. Further dehydration at higher temperature (120 °C), however, leads to a poorer catalytic performance.